The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/nvsm.1561
|View full text |Cite
|
Sign up to set email alerts
|

Cause-related events: fulfilling the objectives of social partnerships

Abstract: Cause‐related events are growing in frequency and popularity. These events enable corporates and not‐for‐profit organisations to collaborate for mutual benefit, within the strategic framework of a social partnership. However, while anecdotal evidence indicates that millions of dollars are invested in events, less is known about how the strategic objectives of social partnerships are achieved via cause‐related events. We present the findings of an ethnographic study of two social partnerships and contribute ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Nas alianças sociais estudadas, não foi destacada a assimetria de poder ou dificuldade de integração e sinergia entre as organizações participantes, corroborando Tsarenko e Simpson (2017). O interesse genuíno das organizações parceiras pela causa trabalhada em conjunto foi essencial para que essas dificuldades não fossem identificadas (Lyes Palakshappa, Bulmer, 2016).…”
Section: Figura 2 Similaridades Dos Componentes Das Dimensões Das Cap...unclassified
See 1 more Smart Citation
“…Nas alianças sociais estudadas, não foi destacada a assimetria de poder ou dificuldade de integração e sinergia entre as organizações participantes, corroborando Tsarenko e Simpson (2017). O interesse genuíno das organizações parceiras pela causa trabalhada em conjunto foi essencial para que essas dificuldades não fossem identificadas (Lyes Palakshappa, Bulmer, 2016).…”
Section: Figura 2 Similaridades Dos Componentes Das Dimensões Das Cap...unclassified
“…Além disso, a 'Diversidade cultural' e as 'Normas comportamento' existentes não se mostraram prejudiciais às parcerias estudadas.Nas alianças sociais estudadas, não foi destacada a assimetria de poder ou dificuldade de integração e sinergia entre as organizações participantes, corroborando Tsarenko eSimpson (2017). O interesse genuíno das organizações parceiras pela causa trabalhada em conjunto foi essencial para que essas dificuldades não fossem identificadas(Lyes Palakshappa, Bulmer, 2016).Quando se refere aos benefícios da coordenação, os achados empíricos também corroboram Tsarenko e Simpson (2017), uma vez que os autores apontam as vantagens aos parceiros quando as trocas de recursos vão além dos recursos financeiros (como trabalho voluntário dos colaboradores da organização parceira e mentoria de gestão). As OSCs podem se beneficiar dos conhecimentos de negócios das empresas, como mencionado porBerger et al (2004) e Liu e Ko (2011); e seu conhecimento acerca dos problemas sociais enfrentados pelo público-alvo da aliança social são um benefício para as organizações parceiras(Sakarya et al, 2012).Ainda, nenhum dos casos apresentou falta de confiança, considerado um dos principais problemas que podem surgir em uma cooperação, como destacado por diversos autores(Álvarez-González et al, 2017;Andrews & Entwistle, 2010;Jamali, Yianni, Abdallah, 2011;Sanzo et al, 2015;Tsarenko & Simpson, 2017).…”
unclassified
“…Partnerships between NPO and FPO can be defined as relationships formed to address social causes that actively engage the partners on an ongoing basis and can be transactional, short-termed and self-interested (Lyes et al , 2016) or more integrative and common interest oriented (Selsky and Parker, 2005). Several studies have found that NPO and FPO have different reasons to be involved in these partnerships (Omar et al , 2014; Pedersen and Pedersen, 2013; Simpson et al , 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%